The Influence of Work Culture and Incentives on Employee Performance (Study at The Regional Revenue Agency Of Surabaya City) - Ifrohah Ifrohah (Lavish Opulent Education, 2025)
This study aims to examine the influence of work culture and incentives on employee performance at the Regional Revenue Agency (Bapenda) of Surabaya City. This research is motivated by the performance gap of civil servants (ASN) even though the assessment score is generally high, as well as the realization of income that has not been optimal in recent years. Using a quantitative approach with descriptive and causal design, data were collected from 36 ASN and PPPK employees using total sampling and analyzed using multiple linear regression through SPSS. The results show that work culture and incentives significantly affect employee performance, with incentives having a more dominant effect. The regression model reveals that 63.7% of the variance in performance is explained by two independent variables. The findings suggest that strengthening work culture—especially in the aspects of participation and internalization of core values—alongside a fair and performance-based incentive system, can substantially improve employee performance. The study recommends organizational interventions such as value-based training, participatory decision-making, and output-based incentive reforms to improve the effectiveness and fairness of human resource management in public institutions.